Source Apportionment and Toxic Potency of PM2.5-Bound Polycyclic Aromatic Hydrocarbons (PAHs) at an Island in the Middle of Bohai Sea, China - Lin Qu; Lin Yang; Yinghong Zhang; Xiaoping Wang; Rong Sun; Bo Li; Xiaoxue Lv; Yuehong Chen; Qin Wang; Chongguo Tian; Ling Ji (Atmosphere, 2022)
Polycyclic aromatic hydrocarbons (PAHs) have attracted more attention because of their high atmospheric concentration and toxicity in recent decades. In this study, a total of 60 PM2.5 samples were collected from Beihuangcheng Island in Bohai Sea, China, from August 2017 to March 2018 for analyzing 16 congeners of PAHs (Σ16PAHs). Sources of PAHs were apportioned by a positive matrix factorization (PMF) model and the carcinogenic risk due to exposure to the PAHs was estimated by the toxicity equivalent of BaP (BaPeq). The results showed that the average concentration of Σ16PAHs was 35.3 ± 41.8 ng/m3. The maximum concentration of Σ16PAHs occurred in winter, followed by spring and autumn, and summer. The PMF modeling apportioned the PAHs into four sources, coal combustion, biomass burning, vehicle exhaust, and petroleum release, contributing 43.1%, 25.8%, 24.7%, and 6.39%, respectively. The average ΣBaPeq concentration was 2.32 ± 4.95 ng/m3 during the sampling period, and vehicle exhaust was the largest contributor. The finding indicates that more attention should be paid to reduce the emissions from coal combustion and vehicle exhaust because they were the largest contributors to the PAH concentration in PM2.5 and ΣBaPeq concentration, respectively.